Gold VS Bond: What Is the Safe Haven for the Indonesian and Malaysian Capital Market? - Robiyanto Robiyanto (Gadjah Mada International Journal of Business, 2018)
This study scrutinizes the potency of gold and bonds as safe haven assets for the Indonesian and Malaysian capital markets, because some previous studies have been undertaken in established market settings. The research period for this study was from June 2008 to September 2016. The quantile regression technique was used to analyze the data. The results of this study indicated that gold did not have a role as a safe haven for the Indonesian capital market, but did have a role as the safe haven for the Malaysian capital market. This study also found that Indonesian government bonds, Malaysian government bonds, and Malaysian corporate bonds could not act as safe haven assets. In contrast, corporate bonds in Indonesia had the potency to perform the function of a safe haven for stocks on the Indonesian Stock Exchange.